Suppression of Huntington's disease pathology in Drosophila by human single-chain Fv antibodies. - Wolfgang, W.J.; Miller, T.W.; Webster, J.M.; Huston, J.S.; Thompson, L.M.; Marsh, J.L.; Messer, A. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
Misfolded neuronal proteins have been identified in a number of neurodegenerative disorders and have been implicated in the pathogenesis of diseases that include Alzheimer's disease, Parkinson's disease, prion-based dementia, Huntington's disease (HD), and other polyglutamine diseases. Although underlying mechanisms remain the subject of ongoing research, it is clear that aberrant processing, protein degradation, and aggregate formation or spurious protein association of the abnormal neuronal proteins may be critical factors in disease progression. Recent work in these diseases has demonstrated in vitro that specific engineered antibody species, peptides, or other general agents may suppress the formation of aggregates. We have modified an approach with intracellularly expressed single-chain Fv (sFv) antibodies (intrabodies) that bind with unique HD protein epitopes. In cell and tissue culture models of HD, anti-N-terminal huntingtin intrabodies (C4 sFv) reduce aggregation and cellular toxicity. Here, we present the crucial experiment of intrabody-mediated in vivo suppression of neuropathology, using a Drosophila model of HD. In the presence of the C4 sFv intrabody, the proportion of HD flies surviving to adulthood increases from 23% to 100%, and the mean and maximum lifespan of adult HD flies is significantly prolonged. Neurodegeneration and formation of visible huntingtin aggregates are slowed. We conclude from this investigation that engineered intrabodies are a potential new class of therapeutic agents for the treatment of neurodegenerative diseases. They may also serve as tools for drug discovery and validation of sites on mutant neuronal proteins that could be exploited for rational drug design.